Perceptions of genetic risk, testing, and counseling among individuals with eating disorders. Issue 9 (15th July 2020) - Michael, Julianne E.; Bulik, Cynthia M.; Hart, Sarah J.; Doyle, Lauren; Austin, Jehannine
Abstract: Objective: Eating disorders develop as a result of genetic and environmental factors. Given that they are multifactorial conditions with a genetic component, they fall within the scope of practice for genetic counseling, but people with these conditions are rarely referred. The purpose of this study was to explore the perceptions of causes of eating disorders, recurrence risk, and interest in genetic counseling and testing among individuals with eating disorders. Method: An online survey comprising both multiple choice and free form text questions, vignettes about genetic counseling, and the ED100K (validated eating disorder diagnostic questionnaire) was shared via support organizations and prominent bloggers in the eating disorders community to recruit individuals with a personal history of an eating disorder from November 2018 to February 2019. Results: In total, 107 participants completed the survey. They perceived that both experiences and genetics were important factors in the development of their eating disorder. All responding participants overestimated the risk for recurrence of eating disorders in children, often by a large margin, and a notable minority reported that their experience with an eating disorder had a negative influence on their childbearing decisions. After imagined experience of genetic counseling, participants reported significantly decreased feelings of stigma, shame, and guilt. Most participants expressed interest in genetic counseling; fewer were interested in genetic testing. Discussion: Genetic counseling may benefit individuals with eating disorders by providing accurate recurrence risk information and reducing feelings of guilt, stigma, and shame, which may in turn encourage earlier support seeking and recovery.